(untitled) (Quinto Sol, 2021)
In this article I analyze the worker-student alliance in the city of Córdoba, Argentina, during the sixties. I argue that the closeness between workers and students was not only built and deployed through their political and union ties. Since the working class was not isolated from the students and the community, their union also had a substantive articulation in everyday life, through innovative educational experiences, family and neighborhood ties that enabled a common sociability. With that idea, I explore the participation of workers in those experiences that were part of the social transformation processes that began in the ‘50s and that I understand as facilitators of additional connections with students.